EVALUASI KEPUASAN KONSUMEN TERHADAP PELAYANAN KEFARMASIAN DI APOTEK KOTA YOGYAKARTA - Baroroh, Faridah (Universitas Ahmad Dahlan, 2014)
Customer satisfaction with pharmaceutical care in pharmacy can be measured bycomparing the expectations of consumers on the quality of pharmacy services desired by thefact that it received. This study was aimed to identify the dimensions of the expected quality ofpharmaceutical care, is considered important, and which has a good performance with a modelof quality pharmaceutical care to costumer at pharmacy in Yogyakarta. This study wasobservational descriptive method and the results are presented with quadrant diagram. Theresults showed that the costumer at pharmacy in Yogyakarta satisfied with pharmaceutical carein Tangible and Empathy dimension. The Tangible and Empathy dimensions are in quadrant IIof the diagram. Howefer, the Assurance, Responsiveness and Reliability dimension, costumersless satisfied because the assume of patients if the pharmacy performance is still lower than theexpectations of consumers. That showed the Assurance, Responsiveness and Reliabilitydimensions are in quadrant III of the diagram.